The relationship between on-water and off-water performance tests in elite canoe slalom athletes - Vajda, Matej; Krupa, Felix; Pratt, Jaylene; Škáchová, Monika; Kováč, Milan; Cvečka, Ján; Busta, Ján (Frontiers in Sports and Active Living, 2025)
PurposeThis study aimed to evaluate the relationship between on- and off-water performance tests in canoe slalom.MethodsA total of 34 elite canoe slalom athletes, who competed in one of the following categories, namely K1 men (K1M, n = 9), K1 women (K1W, n = 8), C1 men (C1M, n = 9), or C1 women (C1W, n = 8), volunteered for the study. On-water testing consisted of two flat water tests: sprints with turns to both sides (SBS; 2 × 15 m shuttle sprints) and an all-out shuttle test (12 × 15 AOT; 12 × 15 m shuttle sprints). Off-water testing included anthropometric analyses, power output in bench press, pull measurement, and 3 × 200 m performance on a kayak ergometer. Each athlete completed testing over two consecutive days.ResultsThe results showed a significant relationship between the on-water tests (SBS/AOT) and body weight (kg, r = 0.472/0.478), body fat (%, r = 0.451/0.445), Pmax bench press (W, r = 0.748/0.705), Pmax bench pull (W, r = 0.704/0.693), relative Pmax bench press (W/kg, r = 0.735/0.663), relative Pmax in bench pull (W/kg, r = 0.727/0.700), ergo best 200 m (s, r = 0.851/0.884), ergo best mean 200 m (W, r = 0.902/0.922), and ergo 3 × 200 m total time (s, r = 0.842/0.884), determined using the Pearson correlation coefficient.ConclusionBased on the identified relationships, we recommend regular monitoring of the physical fitness levels of canoe slalom athletes using the described off-water tests. These tests can help identify the strengths and weaknesses of athletes, enabling coaches to optimize the training process.